2019
DOI: 10.1111/jce.14194
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate noise detection in Tendril family pacing leads

Abstract: Introduction Noise oversensing encountered in patients with Abbott Tendril leads in our hospital triggered an internal investigation. Methods We retrospectively analyzed patients with a Tendril lead model 1688, 1788, 1888, and 2088. Most leads were connected to Abbott generators. To exclude a primary generator issue as the cause of noise oversensing, we enrolled a cohort of patients in whom Medtronic CapSureFix leads model 4076 and 5076 were prospectively connected to similar Abbott generators. Results A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Several other studies have since been published (Table 1). 4–6 All of these studies consistently showed that the rate of electrical abnormalities noted with Tendril leads vary from 6%‐19% as compared to less than 2% with non‐Tendril leads over 4–5 years of follow‐up. These results remained true in patients with Abbott and non‐Abbott generators.…”
Section: Tendril Leads (#) F/u (Years) Tendril Failure Rate (%) Comparator Failure Rate (%) ↑Failure With Optim‐insulated Leads Abbott Gementioning
confidence: 87%
“…Several other studies have since been published (Table 1). 4–6 All of these studies consistently showed that the rate of electrical abnormalities noted with Tendril leads vary from 6%‐19% as compared to less than 2% with non‐Tendril leads over 4–5 years of follow‐up. These results remained true in patients with Abbott and non‐Abbott generators.…”
Section: Tendril Leads (#) F/u (Years) Tendril Failure Rate (%) Comparator Failure Rate (%) ↑Failure With Optim‐insulated Leads Abbott Gementioning
confidence: 87%